An optimized robust watermarking technique using CKGSA in frequency domain. (May 2021) - Singh, Roop; Ashok, Alaknanda
Abstract: The existing SVD based watermarking techniques insert watermark into the singular component which causes the false positive problem (FPP). To overcome this problem, a robust watermarking technique using a chaotic kbest gravitational search algorithm (CKGSA) in DCT and SVD domain is proposed. To eliminate the FPP, the watermark is embedded into the principal component (PC) of the cover image rather than the singular value. The objective to use CKGSA is to optimize the value of multiple embedding factors so that robustness and imperceptibility can be balanced. Arnold transform (AT) is applied to the watermark image before embedding, to enhance security and robustness. The performance of the proposed technique has been experimented on a standard dataset and compared with the six recent state-of-the-art techniques including DS-DE, DS-PSO, DCT-SVD, DDS-PSO, DS-GSA, and DS-TLBO in terms of imperceptibility (PSNR, SSIM) and robustness (PSNR, NC). The experimental results demonstrate that the proposed technique outperforms the other existing techniques.